Dissociative symptoms and neuroendocrine dysregulation in depression - Bob, Petr; Fedor-Freybergh, Peter; Jasova, Denisa; Bizik, Gustav; Susta, Marek; Pavlat, Josef; Zima, Tomas; Benakova, Hana; Raboch, Jiri (Medical science monitor, 2008)
BACKGROUND: Dissociative symptoms are traditionally attributed to psychological stressors that produce dissociated memories related to stressful life events. Dissociative disorders and dissociative symptoms including psychogenic amnesia, fugue, dissociative identity-disorder, depersonalization, derealization and other symptoms or syndromes have been reported as an epidemic psychiatric condition that may be coexistent with various psychiatric diagnoses such as depression, schizophrenia, borderline personality disorder or anxiety disorders. According to recent findings also the somatic components of dissociation may occur and influence brain, autonomic and neuroendocrine functions. At this time there are only few studies examining neuroendocrine response related to dissociative symptoms that suggest significant dysregulation of the hypothalamus-pituitary-adrenal (HPA) axis. The aim of the present study is to perform examination of HPA axis functioning indexed by basal cortisol and prolactin and test their relationship to psychic and somatoform dissociative symptoms. MATERIAL/METHODS: Basal cortisol and prolactin and psychic and somatoform dissociative symptoms were assessed in 40 consecutive inpatients with diagnosis of unipolar depression mean age 43.37 (SD=12.21). RESULTS: The results show that prolactin and cortisol as indices of HPA axis functioning manifest significant relationship to dissociative symptoms. Main results represent highly significant correlations obtained by simple regression between psychic dissociative symptoms (DES) and serum prolactin (R=0.55, p=0.00027), and between somatoform dissociation (SDQ-20) and serum cortisol (R=-0.38, p=0.015). CONCLUSIONS: These results indicate relationship between HPA-axis reactivity and dissociative symptoms in unipolar depressive patients that could reflect passive coping behavior and disengagement.
Keywords: Hydrocortisone; Hypothalamo-Hypophyseal System; Adult; prolaktin; Male; Dissociative Disorders; lidé; lidé středního věku; Humans; disociační poruchy; Middle Aged; Stress, Psychological; Prolactin; průzkumy a dotazníky; depresivní poruchy; systém hypotalamus-hypofýza; Depressive Disorder; životní změny; systém hypofýza - nadledviny; psychický stres; Life Change Events; mužské pohlaví; dospělí; ženské pohlaví; Female; hydrokortison; Pituitary-Adrenal System; Surveys and Questionnaires